1983
DOI: 10.1159/000214711
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclooxygenase Inhibition on Platelet-Vessel Wall Interaction

Abstract: Prostaglandins play an important role in the platelet-vessel wall interaction. Acetylsalicylic acid inhibits the cyclooxygenase activity within the vessel wall. Continuous superfusion with acetylsalicylic acid induces a rapid, but evanescent decrease in thromboformation. The trigger mechanism involved could be related to the ratio of cyclic endoperoxides (PGG2 and PGH2) versus prostacyclin (PGI2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Like statins, aspirin has been shown to possess neuroprotective properties by inhibiting glutamatergic excitotoxicity caused by hypoxia 14 . In addition, aspirin inhibits the enzyme cyclo‐oxygenase which is involved not only in mediating inflammation but also in promoting platelet aggregation; 18,19 it may thus improve optic nerve perfusion by stabilizing microcirculatory flow 20 . One study has found a correlation between aspirin use and increased utilization of surgical management in primary OAG patients, 21 but this finding was attributed to the high incidence of comorbid systemic illnesses in patients taking aspirin.…”
Section: Discussionmentioning
confidence: 99%
“…Like statins, aspirin has been shown to possess neuroprotective properties by inhibiting glutamatergic excitotoxicity caused by hypoxia 14 . In addition, aspirin inhibits the enzyme cyclo‐oxygenase which is involved not only in mediating inflammation but also in promoting platelet aggregation; 18,19 it may thus improve optic nerve perfusion by stabilizing microcirculatory flow 20 . One study has found a correlation between aspirin use and increased utilization of surgical management in primary OAG patients, 21 but this finding was attributed to the high incidence of comorbid systemic illnesses in patients taking aspirin.…”
Section: Discussionmentioning
confidence: 99%
“…Not long after the development and introduction of the first NSAIDs in the late seventies, the first reports on side effects in the cardiovascular and renal systems started to appear. Relationships between the inhibition of COX and platelet thrombus formation [103] and occasional decreases in glomerular filtration rate and re¬nal function [104] were reported as early as 1980s. Al-though some contradictory results have been obtained throughout the years, the evidence point out to a certain increase of the risk of cardiovascular incidences, espe-cially when high doses are administered on a long-time basis.…”
Section: Side Effects Of Cyclooxygenase-2 Inhibitorsmentioning
confidence: 99%